2018
DOI: 10.1016/j.scitotenv.2018.05.301
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter and estrogen interactions regulate estrogen removal in the aqueous environment: A review

Abstract: This review summarizes the characterization and quantification of interactions between dissolved organic matter (DOM) and estrogens as well as the effects of DOM on aquatic estrogen removal. DOM interacts with estrogens via binding or sorption mechanisms like π-π interaction and hydrogen bonding. The binding affinity is evaluated in terms of organic-carbon-normalized sorption coefficient (Log K) which varies with types and composition of DOM. DOM has been suggested to be a more efficient sorbent compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(19 citation statements)
references
References 112 publications
1
18
0
Order By: Relevance
“…Many studies have confirmed that the difference in the toxicity of endocrinedisrupting chemicals varies widely between species (Perron and Juneau 2011;Salomao et al 2014;Xiang et al 2018). Environmental levels of hormones in typical lakes and rivers from different countries fluctuate in the range of ng L −1 (Adeel et al 2017;Ma and Yates 2018). The ecological risk of these compounds can be assessed by comparing the measured environmental concentrations and the EC 50 values obtained in this study.…”
Section: Discussionsupporting
confidence: 51%
“…Many studies have confirmed that the difference in the toxicity of endocrinedisrupting chemicals varies widely between species (Perron and Juneau 2011;Salomao et al 2014;Xiang et al 2018). Environmental levels of hormones in typical lakes and rivers from different countries fluctuate in the range of ng L −1 (Adeel et al 2017;Ma and Yates 2018). The ecological risk of these compounds can be assessed by comparing the measured environmental concentrations and the EC 50 values obtained in this study.…”
Section: Discussionsupporting
confidence: 51%
“…Estrogens can offer the risks because they act as endocrine disruptors (EDCs) resulting in fish feminization [190] and influencing plant or human health. Estrogens are excreted through urine, primarily [191]. The investigation of estrogens and their analogues in human urine has become indispensable for the health of women due to the above reasons.…”
Section: Hormonesmentioning
confidence: 99%
“…Hence, the migration of phenanthrene in natural freshwater may be dominated by some geochemical factors. The dissolved organic matter in the sediment might be the main factor that affects the transfer of those pollutants [63][64]. The adsorption process mainly occurred between the organic matter on the sediment and the phenanthrene in 0-2 h. While with the organic matter escaping from sediment in stirring conditions [65][66], the phenanthrene adsorbed onto the organic matter enter the water phase again in 2-24 h (Fig.…”
Section: Implications For Phenanthrene Reactivity In the Estuarine Areamentioning
confidence: 99%